Linguistic Equity in Digital Age Education: A Critical Examination of Language Hierarchies, Technological Bias, and Multilingual Pedagogies - Badawi, Habib (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
The digital revolution in education has ushered in unprecedented opportunities for language learning, yet it has simultaneously perpetuated and amplified deep-seated linguistic inequalities that mirror broader colonial and imperial legacies. This comprehensive study interrogates the mechanisms through which digital educational technologies systematically reinforce linguistic hierarchies, marginalizing multilingual learners through algorithmic biases and persistent monolingual orientations embedded within their fundamental architectures. By employing a sophisticated mixed-methods approach that combines critical discourse analysis of dominant platforms, including Duolingo, Rosetta Stone, and Babbel, with extensive ethnographic case studies of translanguaging classrooms across diverse global contexts, this research unveils the systemic privileging of standardized linguistic varieties such as Received Pronunciation and Castilian Spanish at the deliberate expense of Afro-Hispanic, Indigenous, and regional dialectal variations. Neural translation systems demonstrate stark accuracy disparities when processing low-resource languages, while gamification mechanics consistently penalize authentic translanguaging practices that reflect natural multilingual communication patterns. However, classrooms that have courageously adopted critical multilingual digital pedagogies demonstrate significantly enhanced learner engagement, heightened metalinguistic awareness, and stronger heritage language retention rates. This study advances a novel theoretical framework termed critical multilingual digital pedagogy, which synthesizes translanguaging theory with critical technology studies and algorithmic justice principles. It contributes actionable design principles for developing more equitable educational technologies while underscoring the urgent necessity of centering linguistic human rights within contemporary digital education policy frameworks.